PEMBUATAN CONCRETE ZEOLIT-LEMPUNG UNTUK PERVAPORASI CAMPURAN ETANOL/AIR TANPA PEMANASAN - Wisnu Adhi Putra, I Made; Arryanto, Yateman; Kartini, Indriana (Prosiding Seminar Nasional MIPA, 2012)
ABSTRACTPreparation of zeolite-clay concrete for new ethanol/water pervaporation without heating has been carried out. Concrete was made by mixing natural zeolite, portland cement, natural clay and distilled water in porcelain disk. The mixture was manually stirred until homogenous suspension obtained. The suspension formed was then placed in the mold and allowed to dry in open air for 48 hours. The mass of natural zeolite was varied from 10, 12.5, 15, 17.5, and 20 g meanwhile the mass of natural clay was varied from 0, 1.25, 2.5, 3.75, and 5 g. The mass of portland cement was fixed in the value of 10 g. The concrete was characterized by infrared spectrophotometer (IR) and X-ray diffraction (XRD). Material testing machine was used to determine the compressive strength of the concrete agreeable with decided ASTM C349-08 standard.Based on preparation of zeolite-clay concrete, it was found that the increase of the natural zeolite mass from 15 to 20 g caused fracture to the concrete, but water adsorption percentage increased from 27.7% to 35.2%. Meanwhile, the higher the mass of natural clay, the greater the compressive strength of concrete from 130.3 MPa to 179.9 MPa and water adsorption percentage from 28.9% to 32.3%. The adsorption-desorption data showed that the water was faster to adsorb into the concrete than ethanol, whereas the desorption rate of concrete with respect to ethanol was greater than that to water. The difference on desorption rate was then used to separate ethanol/water mixture through pervaporation without heating. Pervaporation test using the concretes resulted in the increase of ethanol feed concentration from 60%, 70%, 80%, and 90% to 82.9%, 82.5%, 87.8%, and 93.7% respectively.Keywords: concrete, compressive strength, adsorption-desorption, ethanol/water mixture, pervaporation.